Kajian Yuridis Akta Perjanjian Pengikatan Jual Beli Hak Atas Tanah - Suardi Suardi; Auliah Ambarwati; Abrana Wijaya (Jurnal Litigasi Amsir, 2023)
This research was conducted with the aim of knowing the legal force of the deed of binding sale and purchase agreement on land rights (PPJB) made before a notary/PPAT and to find out the legal protection for the parties in the binding agreement on sale and purchase of land rights (PPJB). The type of research used in this study is normative research, which is a process of finding legal rules, legal principles, and legal doctrines to answer the legal issues at hand. Legal research that examines rules or norms is referred to as normative research, so the research method used is the Normative legal research method which will analyze the Deed of Sale Agreement (PPJB) of Land Rights. Based on the analysis of data and facts, in chapter four above, the following conclusions can be drawn: The legal force of the Sale and Purchase Agreement (PPJB) of Land Rights made before a Notary/PPAT, depending on where the sale and purchase agreement is made, if not before a public official (notary) then it becomes a private deed whereas if it is made by or before public officials, the deed becomes an authentic deed. This is in accordance with Article 1868 of the Indonesian Civil Code that a deed can become an authentic deed if it is made before the authorized public official at the place where the deed was made. And As for the legal protection for the parties, especially the buyer in a sale and purchase agreement that is carried out privately, the legal protection provided in the binding sale and purchase agreement is very strong because of the nature of proof of the binding sale and purchase agreement made before a public official in this case a Notary. Namely by signing the deed in front of a Notary or official appointed for signature validation (such as Consular Officers, Embassies, or Regional Heads starting from the Regent level and above) by explaining the contents first to the parties and then signing in front of a Notary or an authorized public official has very strong evidence in accordance with the evidence from the authentic deed.